Pengaruh Audit Tenure, Kompleksitas Audit, Dan Time Buget Pressure Terhadap Kualitas Audit Di Kantor Akuntan Public Provinsi Bali - Chintya Dewi, Ni Putu Nanna; Dwiyanti, Kadek Trisna (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
This study, which was conducted at the Bali Provincial Public Accountant Office incorporated in IAPI (Indonesian InstituteaofaCertifiedaPublic Accountants), aims to determine the effects ofaaudit tenure, audit complexity, and time budget pressure on audit quality. A total of 65 respondents were sampled, with a non-probabilityisamplingimethod with a purposive sampling technique. The data collection was done through spreading questionnaires and the analysis technique was multiple linear regression. The result showed that the influence of audit tenure, audit complexity, and time budget pressure affected audit quality. Keywords : Audit tenure; audit complexity; timeibudgetipressure;iauditiquality